NPY promotes macrophage migration by upregulating matrix metalloproteinase‐8 expression. Issue 3 (24th July 2020) - Wu, Weiqiang; Peng, Song; Shi, Yanchuan; Li, Linyu; Song, Zhiyuan; Lin, Shu
Abstract: Macrophage migration is thought to participate in obesity‐related cardiovascular diseases. Matrix metalloproteinase‐8 (MMP‐8) possesses proteolytic activity on the extracellular matrix (ECM), which promotes macrophage migration to the site of vascular injury. Neuropeptide Y (NPY) is a bioactive peptide involved in MMP expression. However, it is uncertain whether NPY can regulate the expression of matrix metalloproteinase‐8 (MMP‐8) in macrophages. In this study, wild‐type C57BL/6 and NPY −/− mice were fed a high‐fat diet and subjected to subcutaneous carotid artery injury with ferric chloride, to observe the role of NPY and macrophages in neointima formation. In addition, Raw264.7 cells were treated with NPY and its antagonists to observe MMP‐8 expression and macrophage migration. We found that NPY −/− mice exhibited significantly reduced neointima formation after carotid artery injury. The content of macrophages and MMP‐8 in the neointima and media were also significantly reduced in NPY −/− mice compared with C57BL/6 mice. Moreover, the expression of MMP‐8 in macrophages was also decreased in NPY −/− mice. NPY increased MMP‐8 messenger RNA and protein expression in Raw264.7 cells in vitro, and this effect was abrogated by the Y1R antagonist. In addition, NPY increased the phosphorylation of ERK1/2, which was significantly attenuated by co‐treatment with the Y1R antagonist. Moreover, NPY‐induced MMP‐8 expression could be decreased by the ERK1/2 inhibitor PD98059. Furthermore, NPY promoted macrophage migration across type I collagen in vitro. In conclusion, NPY promotes macrophage migration by upregulating MMP‐8 expression, which we believe to be an underappreciated mechanism of the increased progression of neointima formation. Abstract : We have demonstrated, for the first time to our knowledge, that NPY increases matrix metalloproteinase‐8 (MMP‐8) expression in macrophages, and promotes macrophage migration by activating the ERK 1/2 pathway via Y1R, in vitro. In addition, the ferric chloride model of arterial injury in the NPY −/− mice demonstrated that inhibition of NPY expression could reduce the content of macrophages and MMP‐8 in injured vascular tissue, which may be, at least partly, responsible for the decreased progression of neointima formation.